Molecular Detection and Phylogenetic Analysis of the alkB Gene in Klebsiella oxytoca Strains Isolated from the Gut of Tenebrio molitor - Tsitsi Lynn Mupamhadzi; Oleen Machona; Farisai Chidzwondo; Rumbidzai Mangoyi (The Scientific World Journal)
The challenge in polystyrene disposal has caused researchers to look for urgent innovative and ecofriendly solutions for plastic degradation. Some insects have been reported to use polystyrene as their sole carbon source, and this has been linked to the presence of microbes in their guts that aid in plastic digestion. Thus, this study focuses on the molecular detection and phylogenetic analysis of the alkane-1-monooxygenase (alkB) gene in Klebsiella oxytoca strains isolated from the gut of Tenebrio molitor. The alkB gene encodes for alkane-1-monooxygenase, an enzyme involved in the oxidation of inactivated alkanes. This gene can be used as a marker to assess bacteria’s ability to biodegrade polystyrene. Three bacterial strains were isolated from the guts of T. molitor mealworms and were confirmed using polymerase chain reaction (PCR) of the 16S ribosomal RNA gene. The primers used in the amplification of the 16S ribosomal RNA region were designed using NCBI, a bioinformatics tool. To detect the presence of the alkB gene in the isolated bacterial strains, a set of primers used in the amplification of this gene was manually designed from the conserved regions of the alkB nucleotide sequences of eleven bacterial species from GenBank. TCOFFE online tool was used to align the alkB sequences of the bacteria, while Jalview and ConSurf were used to view the alignment. The amplified alkB gene was then sequenced using the Sanger sequencing technique, blasted on NCBI to look for similar sequences, and a phylogenetic tree was constructed. Based on the 16S ribosomal RNA gene sequences, the isolated bacterial strains were confirmed to be Klebsiella oxytoca NBRC 102593, Klebsiella oxytoca JCM 1665, and Klebsiella oxytoca ATCC 13182. The alkB gene sequence identical to fourteen alkB gene sequences derived from Actinobacteria whole genome was detected in Klebsiella oxytoca for the first time to the best of our knowledge. The novel nucleotide sequence was published in the NCBI database under accession number OP959069. This gene sequence was found to be for the enzyme alkane-1-monooxygenase and may be one of the enzymes responsible for polystyrene degradation by the putative Klebsiella oxytoca ATCC 13182 in T. molitor.